Phytochemical analysis, antioxidant and antifungal activities of Calicotome spinosa (L.) Link. from Eastern Morocco - Siham RAMDANI; Kaoutar ABOUKHALID; Mohammed ELYAKOUBI; Abdelhak KHALLOU; Khalid EL BEKKAYE (Notulae Scientia Biologicae)
Calicotome spinosa, which belongs to the Fabaceae family, is renowned for its richness in secondary metabolites, particularly phenolic compounds, and is commonly used to treat various ailments. In this study, leaves of C. spinosa collected from six distinct localities in Eastern Morocco underwent phytochemical analysis, and their antioxidant and antifungal activities were evaluated. The phytochemical analysis showed that the total polyphenol content ranges between 13.64 and 16.52 mg GAE g–1 of dry extract. The sites of Tinissane and Chouihiya exhibited the highest flavonoid contents, with 10.57 and 10.48 mg RE g–1 respectively. Concerning tannins, the leaves of Sid El Bachir presented the highest content with 5.83 mg CE g–1. Pigment assay results showed a significant difference in chlorophyll content between the different sites, while no significant difference was detected for carotenoids. Regarding antioxidant activity, a significant difference was observed between the inhibition levels of leaves from different sites, and these results were strongly correlated with their total polyphenol contents. For antifungal activity, methanolic extracts showed superior activity against Alternaria alternata, with a fungal growth inhibition rate reaching 44.72%. Conversely, acetone/ethanol extracts were less effective, with inhibition rates not exceeding 17%. These results indicate that local environmental conditions, such as salinity, water stress, high temperatures, and precipitation, as well as extraction methods and solvents used, play a crucial role in the variation of these bioactive compounds.